2017
DOI: 10.1631/jzus.b1700052
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin inhibits fibrosis by modulating the PDGFR/ERK signal pathway: an in vitro study

Abstract: Accumulating evidence indicates that endostatin inhibits fibrosis. However, the mechanism is yet to be clarified. The aim of this study is to evaluate the effect of endostatin on platelet-derived growth factor-BB (PDGF-BB)-or transforming growth factor β1 (TGF-β1)-induced fibrosis in cultured human skin fibroblasts, and to further examine the molecular mechanisms involved. Human dermal fibroblasts were cultured in Dulbecco's modified Eagle's medium (DMEM) and serum-starved for 48 h before treatment. Cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This suggests that the anti-fibrotic effect of endostatin could be mediated by the VEGF pathway, in agreement with the fact that endostatin bind to these receptors [319]. The inhibition of fibrosis by endostatin may also be mediated by the modulation of the PDGFR/ERK signal pathway [326].…”
Section: Collagen Matricryptins/matrikines In Fibrosissupporting
confidence: 67%
See 1 more Smart Citation
“…This suggests that the anti-fibrotic effect of endostatin could be mediated by the VEGF pathway, in agreement with the fact that endostatin bind to these receptors [319]. The inhibition of fibrosis by endostatin may also be mediated by the modulation of the PDGFR/ERK signal pathway [326].…”
Section: Collagen Matricryptins/matrikines In Fibrosissupporting
confidence: 67%
“…Indeed endostatin decreases both PDGF-BB-and TGF-β1-induced over-expression of collagen I in human dermal fibroblasts, and inhibits the expression of PDGFR and p-ERK [326]. The expression of VEGF/VEGFR-2 and the activation of ERK1/2 are inhibited by endostatin, which…”
Section: Collagen Matricryptins/matrikines In Fibrosismentioning
confidence: 89%
“…Endostatin is the C-terminal of collagen type XVIII present in the liver sinusoidal and basement membrane, and discovered to ameliorate liver fibrosis 13. Our previous studies found that endostatin ameliorates scar formation in the rabbit ear model14 and inhibits fibrosis in human fibroblasts 8,15. In the present study, endostatin significantly inhibited the upregulated expressions of collagen I, α-SMA, and F-actin induced by PDGF-BB and TGF-β1 in HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs were treated with 4% (0.04 g/mL) paraformaldehyde solution followed by 0.2% (v/v) Triton X-100. Immunofluorescent staining with the antibody against F-actin was performed according to the manufacturer’s instruction as described previously 8. DAPI reagent (4′,6-diamidino-2-phenylindole, MP Biomedicals, 1:7,500) was used to stain the nucleus.…”
Section: Methodsmentioning
confidence: 99%
“…Suppression of cancer growth by endostatin acts through control of cell phenotype which is seen to ameliorate liver, lung and other fibrotic organs 30,31 . In addition, endostatin elicits anti‐fibrotic properties by reducing TGF‐β‐induced fibrosis through the PDGFR/Erk pathway 32 . In other words, it is a very potent signalling peptide.…”
Section: The Extracellular Matrixmentioning
confidence: 99%